STRATEGI PEMASARAN WISATA DESA PADAK GUAR LOMBOK TIMUR BERBASIS EKONOMI BIRU MELALUI PEMBUATAN VIDEO COMPANY PROFILE - Ati, Aini; Prihatini, Annisa Cahaya Maharani Lombok; Husna, Baiq Nafila; Putri, Gaisha Shofia; Sanjaya, Kiagus Bagas; Kiasatina, Olga Salsabila; Pebbri, Pelin; Sa’ban, Saiful; Dewi, Septyani Nanda; Hardiyanti, Tika (Universitas Mataram, 2024)
The study ran a blue economy based tourist marketing strategy through a company profile video as an effort to boost tourist attraction. The study is carried out in guar district samogata, east lombok district, and research is carried out in August 2024 with 29 people engaging the village of padak guar. As for the conduct of this activity, the production of the company profile video village on padak gaur. This study suggests that after the performance of these social events, people in attendance have suggested that they are aware of the importance of using technology in daily life, primarily promoting the tourist village of padak guar, in order to boost the economy of padak guar village. And the collaboration between the community and the real-life work team working on the community outreach section on the village's instagram feed on padak guar has been successful.